USING LEXICAL AND GRAMMATICAL TRANSFORMATIONS IN , THE ADVENTURES OF SHERLOCK HOLMES AS WELL AS THE HOUND OF BASKERVILLES“ BY ARTHUR CONAN DOYLE - Eshboyeva Mahliyo Sheraliyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The analysis of lexical and grammatical transformations in Arthur Conan Doyle’s "The Adventures of Sherlock Holmes" and "The Hound of the Baskervilles" provides insightful reflections on the linguistic techniques employed in these iconic works. These transformations not only reveal how language shapes the narratives but also demonstrate the stylistic nuances that make the works of Sherlock Holmes distinctive in the realm of detective fiction.